An Anatomical and Clinical Examination of Meridian and Meridian Point - MATSUOKA, Kenji; SAKAGUCHI, Shunji; KITAMURA, Seiichiro; YOSHIDA, Atsushi; MORIKAWA, Kazuhiro; MORI, Shyungo; WANG, Cai Yuan; OZAKI, Tomofumi; TANIGUCHI, Kazuhisa; YAMADA, Kansho; YONEYAMA, Sakae (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 2006)
Six members of the Research Committee for the Meridian Point (former Committee for the Meridian Point) reported on three themes regarding meridian and acupuncture point at Workshop II of the 54th Science Rally of The Japan Society of Acupuncture and Moxibustion held in Fukuoka. 1st theme : Anatomical examination of the meridian and meridian point. 1) Anatomic structure showing path and meridian running. (Kenji Matsuoka) : Similarity of meridian pathway and course of nerve and blood vessels in cadaver. 2) Gross anatomical study of meridian and acupuncture point in upper limbs (Kansho Yamada) : Doctoral study of Katsuyosi Toyoda, former Nagoya City University School of Medicine researcher and Yamada's study (Relation between running of meridian & acupuncture point and subdermal nerve & blood vessels) were reported. 2nd theme : Study of acupuncture safety depth in Japan and China. 1) Research and progress situation of acupuncture safety depth in China. (WANG Cai Yuan) : Data of Yan Zhenguo, professor of anatomy at Shanghai University of Traditional Chinese Medicine, an authority on the study of acupuncture safety depth and progress situation of recent study of acupuncture safety depth in China. 2) Retrospective study of acupuncture safety depth (Tomofumi Ozaki) : Study of acupuncture safety depth published by Ozaki to date and comparative study alongside Prof. Yan Zhenguo data. 3rd theme : Examination of clinical effect of a few meridian points. 1) Acupuncture clinical effect using a few meridian points (Syunji Sakaguchi) : Paper research and analysis of acupuncture clinical effects using 1-4 meridian points of Japana Centra Revuo Medicina. 2) Inflence on skin energizing current by various acupuncture stimulation of LI4 (Gokoku) (Kazuhiro Morikawa) : Influence on the amount of skin energizing current by acupuncture stimulation, direct current electricity stimulation and stimulation of electroacupuncture to LI4.